Experiment, Optimization, and Design of Electromagnetic Track Brake for High-Speed Railways System. (9th March 2020) - Xiang, Chun; Wang, Jun-Cheng; Gu, Yu-Feng; Zhang, Shi-Jin; Chen, Shi-An
Abstract : To enhance braking force and control convenience of high-speed railway systems, this paper proposes a new electromagnetic track brake, and the corresponding design, optimization, and experimental test are implemented. The proposed track brake is longitudinal-axis magnetic circuits excited by multiple coils electromagnets, and the pole shoes are extending outward. A preliminary design of an electromagnetic track brake is developed, including iron core height, iron core width, iron core gap, excitation ampere-turn, coil arrangement form, coil thickness, and preliminary height of single-layer coil. The electromagnet number and pole shoe gap are optimized through three-dimensional electromagnetic simulation comparisons. The final design of the electromagnetic track brake is determined, including iron core length, copper wire diameter, coil turn, and final height of single-layer coil. Experimental verification of electromagnetic attractive force is performed through prototype tests, and the newly developed electromagnetic track brake can enhance electromagnetic braking deceleration by 39%.